2021
DOI: 10.1002/psp4.12672
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of breast cancer resistant protein mediated drug‐drug interactions using physiologically‐based pharmacokinetic modeling

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…Our previous studies, using a large set (n = 42) of OATP1B1 inhibitors, suggested that the clinical DDI risk is likely for inhibitors with R value > 1.5, although a quantitative relationship could not be seen between the R value and statin AUC ratios. 9,26 Later observation may suggest uncertainty in quantitative translation of in vitro Ki to in vivo Ki. In fact, inhibitor-specific in vitro-in vivo disconnect of about 2-fold to 37-fold was noted for OATP1B Ki based on extensive mechanistic PBPK analysis.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies, using a large set (n = 42) of OATP1B1 inhibitors, suggested that the clinical DDI risk is likely for inhibitors with R value > 1.5, although a quantitative relationship could not be seen between the R value and statin AUC ratios. 9,26 Later observation may suggest uncertainty in quantitative translation of in vitro Ki to in vivo Ki. In fact, inhibitor-specific in vitro-in vivo disconnect of about 2-fold to 37-fold was noted for OATP1B Ki based on extensive mechanistic PBPK analysis.…”
Section: Articlementioning
confidence: 99%
“…and OATP1B inhibitors (e.g., rifampicin single dose). An extensively validated rosuvastatin PBPK model was directly adopted from Costales et al 26 The pitavastatin substrate model developed by Duan et al 27 and modified by Kimoto et al, 9 was used as is.…”
Section: Pbpk Modeling and Simulationsmentioning
confidence: 99%
“…On the other hand, the specific uptake of rosuvastatin in our OATP1B1 expression system was not high enough to determine K i,OATP1B1 for CysA to support the substrate dependence in K i,OATP1B between rosuvastatin and CP‐I. We note that, even though CysA has been reported to inhibit BCRP in vitro, 23 in the current analysis, we did not consider inhibition of BCRP‐mediated transport of rosuvastatin by CysA in the PBPK model. This limitation may have resulted in underestimation of the k a and/or F a F g of rosuvastatin when co‐administered with CysA.…”
Section: Discussionmentioning
confidence: 76%
“…Although imperfect, the I gut /IC 50 value of ≥ 10 criterion appears to better predict a potential P-gp DDI than it does when applied to BCRP. 36,37 In fact, in the absence of OATP1B1 inhibition (which applies to abrocitinib), BCRP I gut / IC 50 values of 100-1000 did not necessarily result in an observed clinically meaningful DDI with rosuvastatin.…”
Section: Articlementioning
confidence: 99%